Longitudinal trends in malaria testing rates in the face of elimination in eastern Myanmar: a 7-year observational study - Rae, JD; Landier, J; Simpson, JA; Proux, S; Devine, A; Maude, RJ; Thu, AM; Wiladphaingern, J; Kajeechiwa, L; Thwin, MM; Tun, SW; Nosten, FH (BioMed Central, 2021)
Background Providing at-risk communities with uninterrupted access to early diagnosis and treatment is a key component in reducing malaria transmission and achieving elimination. As programmes approach malaria elimination targets it is critical that each case is tested and treated early, which may present a challenge when the burden of malaria is reduced. In this paper we investigate whether malaria testing rates decline over time and assess the impacts of integrating malaria and non-malaria services on testing rates in the malaria elimination task force (METF) programme in the Kayin state of Myanmar.